Design, development and randomised controlled trial protocol of a smartphone-delivered version of 'SOLAR' for emergency service workers to manage stress and trauma. Issue 2 (10th February 2023) - Metcalf, Olivia; Gibson, Kari; Fredrickson, Julia; Finlayson-Short, Laura; Varker, Tracey; O'Donnell, Meaghan
Introduction: Emergency service workers are routinely exposed to stress and trauma, and there is a need to address mental health symptoms early to prevent chronic impairment and/or psychiatric disorder. Digital health innovations mean that face-to-face psychosocial interventions can now be delivered remotely, which is particularly appealing to populations who have strong preferences for digital delivery, such as emergency service workers. This two phase study aims to first adapt the Skills fOr Life Adjustment and Resilience (SOLAR) programme into a smartphone application ('app'), and then evaluate the effectiveness of this new app. Methods and analyses: First, focus groups and codesign activities with mental health professionals and emergency service workers will be conducted to develop and test the prototype smartphone version of SOLAR (ie, SOLAR-m). Second, a multicentre randomised controlled trial will investigate the effectiveness of the new app, compared with an active control app, in reducing symptoms of anxiety and depression (primary outcome), as well as other indicators of mental health and work performance. Firefighters from one of the largest urban fire and rescue services in Australia who are currently experiencing distress will be invited to participate. After screening and baseline assessment, 240 will be randomised to receive either SOLAR-m or the control app for 5 weeks, with measurements pre, post and 3-month follow-up. Analyses will be conducted within an intention-to-treat framework using mixed modelling. Ethics and dissemination: The current trial has received ethics approval from the University of Melbourne Human Research Ethics Committee (2021-20632-18826-5). Study results will be disseminated through peer-reviewed journals and conferences, with a focus on how to expand the new app to other trauma-affected populations if proven effective. Trial registration number: ANZCTRN12621001141831.